2015
DOI: 10.1182/blood-2014-11-610857
|View full text |Cite
|
Sign up to set email alerts
|

Enoxaparin for prevention of unexplained recurrent miscarriage: a multicenter randomized double-blind placebo-controlled trial

Abstract: Key Points• The use of low-molecularweight heparin did not improve live-birth rates in nonthrombophilic women with consecutive recurrent miscarriage.• Prophylactic doses of lowmolecular-weight heparin should no longer be prescribed in this clinical setting.It is common practice in many centers to offer antithrombotic medications to women with unexplained recurrent miscarriage, in the presence or absence of inherited thrombophilia. Although no benefit of aspirin vs placebo has been clearly demonstrated, a doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
102
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 35 publications
0
102
0
Order By: Relevance
“…Some trials suggest benefit in reducing recurrent early and late pregnancy loss,13 14 as well as reduction in adverse outcomes and placental vasculopathy 15 16. Conversely, a recent double-blinded randomised controlled study by Pasquier et al 17 reported, in keeping with similarly well conducted studies, that LMWH did not improve live birth rates in non-thrombophilic women with previous consecutive recurrent miscarriage 18–20…”
Section: Discussionmentioning
confidence: 97%
“…Some trials suggest benefit in reducing recurrent early and late pregnancy loss,13 14 as well as reduction in adverse outcomes and placental vasculopathy 15 16. Conversely, a recent double-blinded randomised controlled study by Pasquier et al 17 reported, in keeping with similarly well conducted studies, that LMWH did not improve live birth rates in non-thrombophilic women with previous consecutive recurrent miscarriage 18–20…”
Section: Discussionmentioning
confidence: 97%
“…Our results are similar to those in studies reported in the literature. In a similar study, Pasquier et al [14] enrolled 258 pregnant women with a history of unexplained recurrent miscarriage (≥2 consecutive miscarriages before 15 weeks' gestation) and a negative thrombophilia screen. They were randomly assigned to receive one daily subcutaneous injection of 40 mg enoxaparin or placebo until 35 weeks' gestation.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that enoxaparin (40 mg once daily) did not improve the chance of a live birth in nonthrombophilic women with unexplained RPL. [14] In another similar multicentre, randomised controlled trial, Schleussner et al [15] determined whether LMWH increases live birth rates in women with unexplained RPL. They enrolled 449 women, with at least 2 early or 1 late miscarriages, at 5 -8 weeks' gestation after confirmation of a viable pregnancy by ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, its prescription has been increasing more and more since the mid-90s and has been shown to be safe for both mother and foetus, in spite of the passage through placenta. In women suffering from early pregnancy loss, it has been shown to be not efficacious [69][70][71][72]. The EAGer doubleblind, placebo-controlled randomised controlled trial (RCT) recently suggested that also preconception-initiated low-dose aspirin did not significantly improve the likelihood of delivering a live born child in 1078 women with one to two previous pregnancy losses.…”
Section: Interventions In Gvcsmentioning
confidence: 99%